ANALISIS PENERAPAN STRATEGI DIFERENSIASI DAN PENGARUHNYA TERHADAP KEPUASAN PELANGGAN PADA PT. TIKI RIAU CABANG PEKANBARU - Yogi, Fri; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Differentiation strategy is a set of integrated measures designed to produce and offer goods / services which are considered by different customers in the things that are important and unique for their customers. Satisfaction is the level of one's feelings after comparing the performance (or outcome) that he felt compared to expectations .Tiki as one freight company must be able to survive from the times to increase competition. for the creation of customer satisfaction, therefore Tiki has a business concept in the form of freight services and money to place into the goal, trying to continue to get closer to its customers.The results of this study indicate that the strategy of differentiation effect on customer satisfaction. It can be seen from the results in the know t (11.444)> t table (1.985) and Sig (0,000) <0.05. This means that differentiation strategy variables significantly influence customer satisfaction. From the above analysis it can be concluded that the influence of the strategy of differentiation and customer satisfaction at PT. Tiki Riau Branch Pekanbaru.Keywords: Differentiation Strategy, Customer Satisfaction.